Single stage auction clearing model for electricity market considering congestion - R.R. Lekshmi; S. Balamurugan (Results in Engineering)
Electric power grid liberalization is adapted worldwide with the intent to lower the electricity prices for end users. The market clearing procedure deployed by the operator can result in power flows which are incompatible with the transfer capacity of the grid, resulting in congestion. Redispatch, nodal and zonal pricing, and congestion management market approaches are employed to tackle congestion. The solutions proposed in congestion management market and fixation of prices while exploiting the power of optimizing models, involve multi-stage approach deploying market clearance, power flow and congestion evaluation, and redispatch through pricing. This article suggests a single step solution to clear the day ahead electricity market while managing congestion in transmission line. The approach involves modelling of the market clearing mechanism as an optimization problem with the aim of maximizing the producer and consumer surplus, meeting the power equilibrium while maintaining the line power flows within the limit. A generalized mathematical model of the problem is formulated in MATLAB Live editor and deployed on an IEEE 5-bus system, while considering two different line limit conditions. The proposed model clears the market without congestion through an optimal compromise in global surplus by 3512.10 INR and 8213.00 INR along with the congestion cost of 2728.30 INR and 6401.60 INR respectively for the testing conditions. The single step solution to the system operator with market price for each area ensuring economic benefit without congestion is ensured.